Prevalence of hypomagnesemia and its association with clinical outcomes in patients with acute coronary syndromes - Munir Ahmad; Muhammad Yasir; Omer Qadeer; Farah Naz; Ahmad Salman; Jasia Shahid (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Acute coronary syndromes (ACS), including unstable angina, NSTEMI, and STEMI, remain the leading causes of morbidity and mortality. Hypomagnesemia (<1.7 mg/dL) occurs in 29–76% of ACS patients and predicts worse outcomes, including arrhythmia’s, larger infarction size, and higher in-hospital mortality. Limited studies have explored its prevalence and prognostic value in low- and middle-income countries like Pakistan. This study aimed to assess the prevalence of hypomagnesemia in ACS patients and its impact on early clinical outcomes. METHODOLOGY: This descriptive cross-sectional study was conducted over one year at Faisalabad Institute of Cardiology, Faisalabad. A total of 185 ACS patients were recruited through consecutive sampling. Serum magnesium was measured within 24 hours of admission. Clinical outcomes, including arrhythmia’s, infarction size, and in-hospital mortality, were analyzed using SPSS 25. RESULTS: Hypomagnesemia was observed in 85(45.9%) of patients. Those with hypomagnesemia had significantly higher rates of arrhythmia’s (41.2% vs. 20%, p≤0.001), larger infarction size (52.9% vs. 30%, p≤0.001), and higher in-hospital mortality (23.5% vs. 10%, p=0.012). Logistic regression identified hypomagnesemia (OR: 2.5, p=0.01), advanced age (OR: 1.8, p=0.03), and diabetes (OR: 1.6, p=0.04) as key predictors of mortality. CONCLUSION: Hypomagnesemia is common in ACS and linked to poor outcomes. Routine screening and management, especially in resource-limited settings, are crucial. Further studies are needed to confirm findings and optimize treatment strategies.